A-Z of your head [ - Baxter, Amanda; Fairbank, L.; Rosenberg, Mike (Channel Four Television Corporation, 2005)
Looks at the variety of mental health issues that affect young people; tries to de-stigmatise mental health problems and encourage young people to talk openly about their feelings; and races through the alphabet, covering a range of questions and issues